2020
DOI: 10.1017/s0967199420000131
|View full text |Cite
|
Sign up to set email alerts
|

Stereological study of organelle distribution in human oocytes at metaphase I

Abstract: Summary We have previously presented a stereological analysis of organelle distribution in human prophase I oocytes. In the present study, using a similar stereological approach, we quantified the distribution of organelles in human metaphase I (MI) oocytes also retrieved after ovarian stimulation. Five MI oocytes were processed for transmission electron microscopy and a classical manual stereological technique based on point-counting with an adequate stereological grid was used. Kruskal–Wallis and Mann–Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 106 publications
(214 reference statements)
0
2
0
Order By: Relevance
“…The quantitative analysis of the 3D image data indicated that, in our samples of maturing human oocytes, mitochondrion occupies approximately 4.26% cytoplasm volume (Figure 2J). This result derived from densely recorded 3D datasets provide a more accurate estimate than the previous TEM stereological studies using 2D image data (Pires-Luís et al, 2016;Coelho et al, 2020).…”
Section: Resultsmentioning
confidence: 62%
“…The quantitative analysis of the 3D image data indicated that, in our samples of maturing human oocytes, mitochondrion occupies approximately 4.26% cytoplasm volume (Figure 2J). This result derived from densely recorded 3D datasets provide a more accurate estimate than the previous TEM stereological studies using 2D image data (Pires-Luís et al, 2016;Coelho et al, 2020).…”
Section: Resultsmentioning
confidence: 62%
“…The quantitative analysis of the 3D image data indicated that, in our samples of MI and MII oocytes, mitochondrion occupies approximately 4.26 % cytoplasm volume (Figure 2J). This result provides a more accurate estimate than previous 2D stereological studies [7,8].…”
mentioning
confidence: 48%